2008
DOI: 10.1063/1.2957066
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal ferrites for use in microwave notch filters and phase shifters

Abstract: Recently there has been interest in small, planar, high frequency (10–50 GHz) signal processing devices which are based on metallic ferromagnets. This paper, in contrast, presents theoretical results for devices utilizing a hexagonal ferrite. The notch filter results show attenuation of frequencies in the 40–60 GHz range with applied fields in the 1–5 kOe range. For geometries similar to the ultrasmall metallic devices, the transmission loss at the notch can be from 20 to 140 dB/cm depending on the thickness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
5
16
0
Order By: Relevance
“…It should be noted that previous theoretical calculations for microstrip geometry had shown that the position of the dip in transmission did not necessarily occur at the same frequency as the maximum absorption in a FMR experiment. 20 The field correction found here is consistent, in magnitude and sign, with the shift found in Ref. [20].…”
Section: Millimeter Wave Phase Shifterssupporting
confidence: 77%
See 4 more Smart Citations
“…It should be noted that previous theoretical calculations for microstrip geometry had shown that the position of the dip in transmission did not necessarily occur at the same frequency as the maximum absorption in a FMR experiment. 20 The field correction found here is consistent, in magnitude and sign, with the shift found in Ref. [20].…”
Section: Millimeter Wave Phase Shifterssupporting
confidence: 77%
“…20 The field correction found here is consistent, in magnitude and sign, with the shift found in Ref. [20].…”
Section: Millimeter Wave Phase Shifterssupporting
confidence: 77%
See 3 more Smart Citations